Role of Charge and Hydrophobic Interactions in the Action of Bactericidal/Permeability-increasing Protein of Neutrophils on Gram-negative Bacteria - Weiss, Jerrold (1983)
We have recently provided evidence suggesting that the action of purified cationic bactericidal/permeability-increasing protein (BPI) from neutrophils on susceptible gram-negative bacteria requires saturation binding to negatively charged surface sites (Weiss, J., S. Beckerdite-Quagliata, and P. Elsbach, 1980, J. Clin. Invest., 65: 619-628.) We now show that this charge interaction is necessary but not sufficient to produce the effects of BPI on the envelope and on viability. By altering the hydrophobic properties of the bacterial (outer) membrane, it is possible to separate saturation binding from the biological action of BPI, indicating that steps beyond surface binding are needed for the antibacterial action. Outer membrane properties were modified by (a) reducing temperature during BPI-Escherichia coli interaction; (b) growing E. coli at 42°C to increase the saturated fatty acid content of membrane phospholipids; and/or (c) using smooth E. coli with a natively less fluid outer membrane. Hydrophobic interaction chromatography on phenyl-Sepharose and measurement of sensitivity to the hydrophobic antibiotic rifampicin were used to monitor the changes in hydrophobic properties of the bacterial outer membrane produced by these manipulations. Nearly all BPI can be removed from the bacterial surface by 80 mM MgCl(2) or by trypsin. At 37°C, removal of BPI results in repair of the envelope alterations, but viability is irreversibly lost, even when Mg(2+) is added after only 15 s of exposure of the bacteria to BPI. However, under conditions of reduced outer membrane hydrophobicity, when saturation binding still occurs within 30 s, E. coli can be rescued by addition of Mg(2+) after up to 5-min exposure to BPI, indicating retardation of postbinding steps. We conclude that after initial binding BPI must enter into a hydrophobic interaction with the outer membrane in order to produce its antibacterial effects. These postbinding events reversibly mediate the membrane perturbations and irreversibly trigger the bactericidal action of BPI.